Persepsi mahasiswa terhadap penggunaan program e-learning berbasis LMS pada Mata Kuliah Teknologi Budidaya Perikanan - Amirah Mustarin; Muhammad Wiharto (Seminar Nasional LP2M UNM, 2019)
The rapid development of information and communication technology has brought major changes in all fields, including the education sector. Educators are required to be able to choose and use various types of existing learning media. One alternative that is potentially used in learning is the e-learning learning method using the learning management system. This study aims to (a) find out the application of the LMS-based E-learning model to improve the quality of learning courses in Aquaculture Technology in the UNM Agricultural Technology Education Study Program. (b) To find out the LMS-based E-learning model for increasing interest in learning courses in Aquaculture Technology in the UNM Agricultural Technology Education Study Program. This research is an "ex-post facto" study conducted in the subject of Aquaculture Technology at the UNM Agricultural Technology Education Study Program. The design of this study is that the variables in this study consist of independent variables, namely the perceptions of students on the use of Learning Management System (X1) E-Learning programs, and one dependent variable, namely Student Learning Interest. Data obtained from observations student interest, and test results during the teaching and learning process are analyzed quantitatively. Student perceptions of the ease of use of the LMS-based E-learning program in the Aquaculture Technology course in the UNM Agricultural Technology Education Study Program are in the high category of 70.59%, the benefits are in the very high category of 85.29% and program acceptance is at very high category of 82.35%. Student interest in the subject of Aquaculture Technology in the UNM Agricultural Technology Education Study Program was in the category of interest of 73.53%.